Perbedaan Pemahaman Konsep Ikrar Talak Menurut Putusan Pengadilan Agama dengan Syariat Islam - Nourma Dewi; Femmy Silaswaty (Wajah Hukum, 2019)
This study aims to determine the differences in understanding the concept of talaq pledges according to the decisions of religious courts with Islamic Shari'a. This research is normative legal research. The research approach used in this study is the legislative approach and the conceptual approach. Based on the results of the research and discussion it can be concluded that there is a concept inconsistency between the religious courts that adhere to the Compilation of Islamic law with Islamic Shari'a which includes the fall of divorce, legal remedies, and the enactment of the Islamic period.